2011
DOI: 10.1007/s10340-011-0370-5
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Nepalese entomopathogenic nematodes as biocontrol agents against Holotrichia longipennis Blanch. (Coleoptera: Scarabaeidae)

Abstract: Holotrichia longipennis Blanch. (Coleoptera: Scarabaeidae) is a serious pest of commercial crops in Siduwa, Dhankuta, Nepal. Seven indigenous isolates of entomopathogenic nematodes (Steinernema lamjungense LMT5, S. lamjungense SS4, S. everestense DKP4, S. abbasi CS1, S. sp. KL1, Heterorhabditis indica CK2 and H. indica CK6) were used in a series of bioassays against the insect. All isolates showed an increased dispersal in response to H. longipennis. Nematodes were more attracted towards third instar larvae th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The susceptibility of Chrysomelidae is sometimes higher in the larval stage (Saleh et al 2009), sometimes in the pupal stage (Xu et al 2010) and which stage is more susceptible is sometimes dependent on temperature (Yang et al (2001) and Khatri-Chhetri et al (2011) found that pupae were more susceptible than larvae to EPN. Ramos-Rodríguez et al (2006) found EPN were less efficacious against pupae and adults than larvae of Tribolium castaneum.…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of Chrysomelidae is sometimes higher in the larval stage (Saleh et al 2009), sometimes in the pupal stage (Xu et al 2010) and which stage is more susceptible is sometimes dependent on temperature (Yang et al (2001) and Khatri-Chhetri et al (2011) found that pupae were more susceptible than larvae to EPN. Ramos-Rodríguez et al (2006) found EPN were less efficacious against pupae and adults than larvae of Tribolium castaneum.…”
Section: Discussionmentioning
confidence: 99%
“…However, most success has been achieved against soildwelling pests or pests in cryptic habitats (Williams and Walters 1999;Tomalak et al 2005;Valle et al 2008). Numerous studies have found that the susceptibility of different developmental stages of insect hosts shows great variations to different species or strains of EPNs (Bedding and Molineux 1982;Geden et al 1985;Fuxa et al 1988;Glazer et al 1991;Smits et al 1994;Jansson 1996;Simões and Rosa 1996;Khatri-Chhetri et al 2011). While developing a sustainable management strategy for any local insect pest, it is therefore always advisable to use the right indigenous EPN isolate, as it is more likely to be adapted to the local climatic conditions and host population.…”
Section: Introductionmentioning
confidence: 99%
“…Species and their different instar larvae within the Scarabaeidae and Melolonthidae families frequently present highly variable susceptibilities to EPNs action (Grewal et al 2005 ; Koppenhöfer et al 2006 ; Khatri-Chhetri et al 2011 ). Therefore, it is critical to evaluate species/strain EPNs dose to determine which generates the greatest pathogenicity.…”
Section: Discussionmentioning
confidence: 99%